Performance analysis on self organization based clustering scheme for FANETs using K-means algorithm and firefly optimization - Yashu Pulhani; Ankur Singh Kang; Vishal Sharma (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
With the fast-increasing development of wireless communication networks, unmanned aerial vehicle (UAV) has emerged as a flying platform for wireless communication with efficient coverage, capacity, reliability, and its network is called flying ad-hoc network (FANET); which keeps changing its topology due to its dynamic nature, causing inefficient communication, and therefore needs cluster formation. In this paper, we proposed a cluster formation, selection of cluster head and its members, connectivity and transmission with the base station using the K-means algorithm, and choice of an optimized path for transmission using firefly optimization algorithm for efficient communication. Evaluation of performance with experimental results are obtained and compared using the K-means algorithm and firefly optimization algorithm in cluster building time, cluster lifetime, energy consumption, and probability of delivery success. On comparison of firefly optimization algorithm with firefly optimization algorithm, i.e., K-means algorithm results proved than without firefly optimization algorithm, better in terms of cluster building time, energy consumption, cluster lifetime, and also the probability of delivery success.